Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.18291/njwls.v8is4.111156
|View full text |Cite
|
Sign up to set email alerts
|

Motivation, Migration and Non-standard Employment: A Survey Among Temporary Agency Workers

Abstract: Research suggests that migrants have a greater tendency to end up in nonstandard employment arrangements than native citizens do, but less attention has been paid to motivational differences within and between migrant groups. On the basis of a survey of temporary agency workers in Norway, we investigate the effect of different country backgrounds on the perceived suitability of nonstandard employment (NSE) at present and in the future. For the perceived current suitability, we find less variation between count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Thus, it seems that the main challenge in hospitality operations is how to deal with within week variations in demand, i.e., how to increase staffing flexibility between days. These issues seem difficult in economies like Norway, where strong labor regulations exist, but some exceptions should still be possible similar to non-standard working hours and third-party providers regulations for the hospitality industry (Underthun and Aasland, 2018). F.K.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it seems that the main challenge in hospitality operations is how to deal with within week variations in demand, i.e., how to increase staffing flexibility between days. These issues seem difficult in economies like Norway, where strong labor regulations exist, but some exceptions should still be possible similar to non-standard working hours and third-party providers regulations for the hospitality industry (Underthun and Aasland, 2018). F.K.…”
Section: Discussionmentioning
confidence: 99%
“…Kirves et al (2014) observed that temporary workers largely tended to be women and younger persons, though again volition was not investigated. Underthun and Aasland (2018) stated that motivation differs between migrated and non-migrated groups as compared to the national background. Chambel and Sobral (2019) observed that TAWs mostly opt for temporary arrangement involuntarily, but outsourcing work more voluntarily.…”
Section: Volition Among Temporary Agency Workersmentioning
confidence: 99%
“…To accomplish the above, the effect of specific motivating elements was investigated in strengthening the good cooperation between the frontline employees and the leadership in conditions of suspension of the operation of the hotels. More specifically, the motivating elements examined are related to a) working conditions (Pawirosumarto et al 2017;Underthun 2014), b) financial and intangible reward (Kakarougkas and Stavrinoudis 2021;Koo et al 2020) and c) the leadership of a hotel relationships with employees and between employees and supervisors (Afsar et al 2018;Han and Hwang 2019). ).…”
Section: Introductionmentioning
confidence: 99%